A singular oral appliance to treat obstructive sleep apnea in CPAP non-adherent patients - Denise Fernandes Barbosa; Lilian Chrystiane Giannasi; Liege Maria Di Bisceglie Ferreira; Miguel Meira e Cruz; Marcelo Corrêa Alves; Fausto Berzin (Dental Press Editora, 2020)
ABSTRACT Introduction: The most prescribed treatment option for Obstructive Sleep Apnea (OSA) is CPAP; however, its adherence is limited. Oral Appliance therapy (OAT) is frequently an option or even an adjuvant, being the mandibular advancement Oral Appliance (OAm) the most used prescription. It modifies the upper airway, improving the airway patency. OAm construction is based on the occlusal plane to disocclusion. In this study, the DIORS® appliance was used, a singular OAm, based on Neuro-Occlusal Rehabilitation concepts, that uses Camper's plane as a disocclusion reference, in order to achieve neuromuscular balance and functional stability. Objective: This study primarily aimed to assess the DIORS® effectiveness in relation to clinical and polysomnographic outcomes. It was also evaluated if the use of DIORS® is as effective as titrated CPAP to treat CPAP non-adherent patients. Methods: Twenty patients were included in this study. Objective and subjective clinical data were assessed at a sleep laboratory using all-night polysomnography, and Epworth Sleepiness Scale (ESS), taken at three moments: Baseline, CPAP titration, and using DIORS®. Analysis of respiratory parameters as apnea/hypopnea index (AHI), oxyhemoglobin saturation levels, the arousal index and daytime sleepiness were taken as criteria for a successful OAT. Results: Respiratory and arousal parameters improved in both therapies, while DIORS® promoted a better ESS. Conclusion: Results from the present work support that DIORS® is a viable and effective adjuvant therapy for patients with moderate to severe OSA non-adherent to CPAP.